Developing countries in the GATT legal system - Hudec, Robert E. (New York : Cambridge University Press, 2011)
"A reissue of Robert E. Hudec's seminal study of the situation of developing countries within the international trade system is once again available"-- Provided by publisher
"In this reissued edition of the classic work Developing Countries in the GATT Legal System, Robert E. Hudec's clear insight on the situation of developing countries within the international trade system is once again made available. Hudec is regarded as one of the most prominent commentators on the evolution of the current international trade regime, and this long out-of-print book offers his analysis of the dynamics playing out between developed and developing nations. A significant contribution when the book was first published, this work continues to serve as a thoughtful and important guide to how current and future trade policy must seriously adapt to the demands of the developing world. This new edition includes a new introduction by J. Michael Finger that examines Hudec's work to understand how the GATT got into its current historical-institutional predicament and the lasting impact of his work on current research on international trade systems"-- Provided by publisher
1. Post-war negotiations on trade liberalization -- 2. First decade of the GATT 1948-2957 -- 3. Demands for a new legal relationship 1958-1963 -- 4. Defining the new relationship 1964-1971 -- 5. Testing the new relationship 1972-1979 -- 6. Development in the 1980s - from without substance -- 7. Basic elements of the legal criticism -- 8. Separating legal and economic issues -- 9. Impact of GATT legal policy on internal decision-making -- 10. Impact on decisions in other governments : non reciprocity -- 11. Impact on decisions in other government : preferences -- 12. First steps towards a better legal policy
First published by Gower Publishing Company Limited, 1987
New edition with Introduction by J. Michael Finger published 2011
Includes bibliographical references (p. 195-202) and index
Keywords: General Agreement on Tariffs and Trade (Organization); Foreign trade regulation; Foreign trade regulation -- Developing countries; Tariff -- Law and legislation; Tariff -- Law and legislation -- Developing countries